PENGARUH DUKUNGAN ATASAN, PELATIHAN DAN SUMBER DAYA MANUSIA TERHADAP KEGUNAAN SISTEM INFORMASI AKUNTANSI KEUANGAN DAERAH PADA SKPD DI PEMERINTAHAN KOTA BANJARMASIN - Ruslinda Agustina; Soedjatmiko Soedjatmiko; Zainab Zainab (Dinamika Ekonomi - Jurnal Ekonomi dan Bisnis, 2019)
Abstract, The research aims to prove empirically the influence of superiors' support, training and human resources on the use of regional financial accounting information systems on SKPD in Banjarmasin city government. The sample of research was 91 employees who were made respondents with the help of statistical test software SPSS version 22 for windows. The conclusion of this study is that the variable of superiors' support and training does not influence the use of regional financial accounting information systems in SKPD in Banjarmasin city government. While the human resource variables affect the use of regional financial accounting information systems in the SKPD in Banjarmasin city government.